"We should see her like part of the team": an investigation into care home staff's experiences of being part of an RCT of a complex psychosocial intervention. (2nd January 2020) - Fossey, Jane; Garrod, Lucy; Lawrence, Vanessa; Testad, Ingelin; Stafford, Jane; Murray, Joanna
Abstract: Objectives: To contribute to improvements in the design and delivery of intervention research in care homes by adopting a collaborative approach that listens to the experiences of care home staff who had participated in a clinical trial aimed at optimising and evaluating a psychosocial intervention package for people with dementia. Methods: Qualitative study involving focus group discussions (FGDs) involving 41 staff across 6 care homes with the UK. Inductive thematic analysis was used to identify themes and interpret the data. Results: Three overarching themes emerged as influential: Recognising preparedness; working together and learning more than expected. The findings highlighted the need to be attentive in addressing staff expectations, the value of sustained relationships and recognition of good practice. The FGDs also identified areas of unanticipated learning that staff and managers adopted. Conclusions: The FGDs showed the importance of considering the overall experience of care home staff who are involved in research and the importance of valuing the skills and experience they hold through positive affirmation. There are often unanticipated consequences of research involvement both on staff practice and on relationships which if promoted could help sustain effective ways of working together.